Familial Aggregation and Risk Factors for Prostate Cancer in Affected Individuals - Julio Armando Sánchez Delgado; Nailé Edita Sánchez Lara (Revista Finlay, 2024)
Foundation: prostate cancer is the second leading cause of death in men worldwide. Genetic studies indicate a link between certain genetic mutations, the aggressiveness of this neoplasia, the risk of developing the disease, and patient survival rates. Objective: to determine family aggregation and risk factors in individuals and families affected by prostate cancer. Method: an observational, analytical, longitudinal, and retrospective, case/control study was conducted on the population of the Banes municipality, Holguín province, between May 2021 and May 2022. The universe included the 75 diagnosed individuals and their families. By simple random sampling, the sample (42 cases) was obtained and the control group was formed at a ratio of 3:1 (126 individuals with no history of the disease). Inclusion/exclusion criteria were applied. The following statistics were used: Chi square, Odd Ratio (OR), including probability and confidence interval. The variables were operationalized: age, degree of consanguinity, and risk factors. The family tree was obtained. Results: first- and second-degree relatives of consanguinity showed the highest incidence of disease for both groups. The age group of 75 years and older prevailed. Family aggregation for the disease was demonstrated (X2=31.66 OR=5.84 95 % CI [2.9; 11.6]). Risk factors showed an association for the disease (X2=24.59 p≤0.05). Sedentary lifestyle (X2=16.7 OR=1.2 95 % CI [1.1; 1.4]) and smoking (X2=6.4 OR=1.1 95% CI [1; 1.3]) expressed a highly significant association for colon cancer. Conclusions: first- and second-degree relatives of consanguinity showed a higher incidence of suffering from the disease. The age group of 75 years and older prevailed. The risk factors that showed an association for the disease were: sedentary lifestyle and smoking.